Successful Single Visit Endodontic Using Bioceramic Sealer and Esthetic Restoration with Porcelain Fused to Zirconia: A Case Report - Meidi Kurnia Ariani; Nanik Zubaidah (Health Notions, 2022)
Background: Single visit endodontic therapy may be defined as the conservative non surgical treatment of an endodontically involved tooth, consisting of complete chemomechanical instrumentation and obturation of the root canal system accomplished in one visit. Case: A 35-year-old woman comes with chief complaint on her upper front left tooth. Clinical examination revealed that the tooth #22 had deep caries dan reached the pulp, non vital teeth. Periapical radiolograph showed radiolucent area in the apical area of tooth #22. The diagnosis is necrosis of pulp with asymptomatic apical periodontitis. Case Management: Tooth #22 was treated with single visit root canal treatment using bioceramic sealer followed by fiber post cementation and porcelain fused to zirconia crown. Patients had no longer complain of pain after treatment. Conclusion: Single visit endodontic can successfully eliminate patient complaints and restore tooth function. Keywords: single visit endodontic; bioceramic sealer; porcelain fused to zirconia